PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI MARGOYOSO - Ulin Nihlah; Wijonarko Wijonarko; Sukamto Sukamto (Universitas Muhammadiyah Kuningan, 2019)
The problem studied in this research is whether the learning model Think Pair Share can improve mathematics learning result of third grade students of SD Margoyoso. The purpose this research is to know the influence of Think Pair Share model toward the result of third grade students and rectangular building area. This type of research is quantitative, with the research design True Experimental type used is pretest-posttest control group design. Based the results of research that has been done the researchers obtained the following result, after doing research obtained learning result in three domain, cognitive, affective, psychomotor. Result obtained from hypothesis test calculation by using t test and regression. from calculation t is obtained t count=4.556728 with t table =2.000 H1 accepted if t count>t table because the result of this research show t count=4.556728>t table =2.000 then H1=received and Ho=is rejected. Then use regression test obtained F count =16631.79 F table=4.810 using dk numerator dbreg= 1 and dbres=29 at 5 % level. So F count> F table so Ho is rejected so the regression equation is significant. Can be taken conclusion model Think Pair Share on student learning outcomes